2017
DOI: 10.3389/fmicb.2017.01103
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene, a Methoxylated Resveratrol Derivative, Efficiently Eradicates Planktonic, Biofilm, and Intracellular MRSA by Topical Application

Abstract: Pterostilbene is a methoxylated derivative of resveratrol originated from natural sources. We investigated the antibacterial activity of pterostilbene against drug-resistant Staphylococcus aureus and the feasibility of using it to treat cutaneous bacteria. The antimicrobial effect was evaluated using an in vitro culture model and an in vivo mouse model of cutaneous infection. The minimum inhibitory concentration (MIC) assay demonstrated a superior biocidal activity of pterostilbene compared to resveratrol (8~1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 48 publications
4
56
0
Order By: Relevance
“…Pterostilbene is a methoxylated derivate of resveratrol originating from natural sources like wine grapes or blue berries. Its potent capability against methicillin-resistant Staphylococcus aureus (MRSA) has been related to bacterial membrane leakage, chaperone protein downregulation, and ribosomal protein upregulation [42].…”
Section: Mode Of Antimicrobial Actionmentioning
confidence: 99%
“…Pterostilbene is a methoxylated derivate of resveratrol originating from natural sources like wine grapes or blue berries. Its potent capability against methicillin-resistant Staphylococcus aureus (MRSA) has been related to bacterial membrane leakage, chaperone protein downregulation, and ribosomal protein upregulation [42].…”
Section: Mode Of Antimicrobial Actionmentioning
confidence: 99%
“…It can be concluded that resveratrol penetrates the epidermis, thus supplementing the lipids of its protective layer. Therefore, during the use of the tested emulsion, the hydration level increased (Yang et al, 2017;Igielska-Kalwat J, Tariq Mahmood, 2018;Vries et al, 2018). Figure 5 presents the average changes in the skin hydration level in the control group.…”
Section: Resultsmentioning
confidence: 98%
“…The biofilm was treated by DMD, ciprofloxacin, or CPC at a concentration of 500 mg/ml for 24 h. The three-dimensional structure and thickness of biofilm were detected by Leica TSC SP2 confocal microscopy [10].…”
Section: Biofilm Determined By Confocal Microscopymentioning
confidence: 99%